Penggunaan Media Audio Visual untuk Meningkatkan Hasil Belajar Pendidikan Agama Katolik pada Siswa Kelas VIII SMP Negeri 2 Merauke - Yohanes Hendro Pranyoto; Modesta Nitti (JURNAL PASTORAL KATEKETIK, 2026)
This study aims to delineate the enhancement of learning outcomes in Catholic Religious Education through the implementation of audio-visual media amongst Year 8 students at State Junior High School 2 Merauke. The research employed a collaborative Classroom Action Research (CAR) design, executed across two cycles. The subjects comprised 19 Year 8 students participating in Catholic Religious Education lessons focused on the topic of the Proclamation of Jesus. Data were gathered via observation sheets, daily journals, and formative evaluation sheets. The findings demonstrated a significant improvement: the mean class score rose from 73.43 (Cycle I, n=16) to 77.35 (Cycle II, n=17), yielding a difference of 3.92 points. Furthermore, the percentage of academic mastery increased from 93.75% in Cycle I to 94.11% in Cycle II, whilst 93% of the students who participated in both cycles exhibited an improvement in their scores. These findings indicate that audio-visual media is highly effective in augmenting student motivation, active engagement, and conceptual understanding within Catholic Religious Education, owing to its capacity to present religious content in a concrete and contextualised manner. Consequently, the application of audio-visual media is recommended as a sustainable pedagogical strategy for Catholic Religious Education at the junior secondary school level.